Directory of resources for educational research in the Caribbean - Quamina-Aiyejina, Lynda (UWI. Faculty of Education St. AugustineTT, 1993)
Brings together the contents of the Caribbean Educational Research Information Service (CERIS) database relating to research in progress, researchers, and organizations.